User-driven design of a flexible distance education environment : rationale, lessons learned and future implications - Löfstrand, Magnus; Johansson, Mathias (Sixth International Conference on Creating, Connecting and Collaborating through Computing (C5 2008), 2008)
This paper discusses the challenges inherent in distributed education and presents the development of a distance education environment to meet the needs of educators and geographically dispersed students at Luleå University of Technology in northern Sweden. The design rationale and experiences from teaching in the environment are discussed. During the course of the research, several prerequisites for quality distance education were identified, one of which is the main topic of this paper. Here, the needs identified by the educators who are to se the created environment are discussed. Those needs have led to the design of the environment, including physical spaces, tools and technologies. Our results indicate that it is now possible to design a highly useful environment for distributed education at a much lower cost-to-quality ratio than only a few years ago. Such a system may be created in a way that allows teachers to earn to use the environment selfsufficiently. Thereby, the need for support staff is greatly diminished. The results indicate that the use of appropriate methods and tools lets teachers work in a distributed environment in a way that closely resembles their normal way of work in a teaching situation. In addition, a strategy for future development of the environment, based on the results presented here and on previous research, is suggested. Godkänd; 2008; 20071207 (maglof)